The Performance of Cold-formed Steel Long-span Roof Structure Combined with Laminated Timber: Cold-formed Steel – Laminated Timber Composite. (2017) - Irawati, Inggar Septhia; Awaludin, Ali; Sebastian, Nicholas Padua
Abstract: This paper presents analytical observation results on the performance of CFS-laminated timber composite long-span roof structure attached by laminated timber composite, named as CFS–laminated timber composite. Two dimensional models of a 25 m CFS Vaulted Parallel Chord truss were analyzed separately. One of them was thoroughly assembled using CFS members only and the other one was assembled from composite members. Based on analytical results, the CFS-laminated timber roof truss has a better performance than the CFS roof truss in resisting the external load.